Iowa Birdline update, January 6, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for Januaray 6, 1992. The highlights for the update include sightings of a Prairie Falcon, Snowy Owl and a female American Wigeon. Also included are handwritten notes with sightings of a Pine Warbler, Winter Wren and a Mute Swan. Epson - sheet feed/flatbed